Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan : Studi Kasus Perusahaan Pertambangan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Silvia Febriani Lestari; Ahmad Idris; Dadang Afrianto (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to explain and prove the hypothesis regarding the influence of investment decisions, financing decisions, and dividend policies on firm value in coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This study used a quantitative approach with a purposive sampling method, resulting in 10 companies as research samples. Data analysis was conducted through classical assumption tests to ensure the fulfillment of regression analysis requirements, followed by hypothesis testing using multiple regression analysis. Data processing was carried out using E-Views software version 13. The results showed that partially, investment decisions have a positive and significant effect on firm value, with a probability value of 0.0000, which is smaller than the 0.05 significance level. This finding indicates that the more appropriate a company's investment decisions are, the higher the company's value is reflected in its stock performance in the capital market. Conversely, the financing decision variable does not have a significant effect on firm value, with a probability value of 0.3796, which is greater than 0.05. This indicates that the funding structure, whether derived from equity or debt, did not directly affect firm value during the study period. Similarly, the dividend policy variable did not significantly influence firm value, with a probability value of 0.7493 > 0.05. This means that the amount of dividends distributed was not a determining factor in firm value in the sample studied. However, simultaneously, all three independent variables—investment decisions, financing decisions, and dividend policy—were shown to have a significant effect on firm value, with a probability value (F-statistic) of 0.0000 < 0.05. This confirms that the combination of these three factors collectively contributes to changes in firm value in the coal sub-sector.